The siRNA cocktail targeting interleukin 10 receptor and transforming growth factor-β receptor on dendritic cells potentiates tumour antigen-specific CD8(+) T cell immunity - Ahn, Y-H (Clin Exp Immunol, 2015)
Dendritic cells (DCs) are promising therapeutic agents in the field of cancer immunotherapy due to their intrinsic immune-priming capacity. The potency of DCs, however, is readily attenuated immediately after their administration in patients as tumours and various immune cells, including DCs, produce various immunosuppressive factors such as interleukin (IL)-10 and transforming growth factor (TGF)-β that hamper the function of DCs. In this study, we used small interfering RNA (siRNA) to silence the expression of endogenous molecules in DCs, which can sense immunosuppressive factors. Among the siRNAs targeting various immunosuppressive molecules, we observed that DCs transfected with siRNA targeting IL-10 receptor alpha (siIL-10RA) initiated the strongest antigen-specific CD8(+) T cell immune responses. The potency of siIL-10RA was enhanced further by combining it with siRNA targeting TGF-β receptor (siTGF-βR), which was the next best option during the screening of this study, or the previously selected immunoadjuvant siRNA targeting phosphatase and tensin homologue deleted on chromosome 10 (PTEN) or Bcl-2-like protein 11 (BIM). In the midst of sorting out the siRNA cocktails, the cocktail of siIL-10RA and siTGF-βR generated the strongest antigen-specific CD8(+) T cell immunity. Concordantly, the knock-down of both IL-10RA and TGF-βR in DCs induced the strongest anti-tumour effects in the TC-1 P0 tumour model, a cervical cancer model expressing the human papillomavirus (HPV)-16 E7 antigen, and even in the immune-resistant TC-1 (P3) tumour model that secretes more IL-10 and TGF-β than the parental tumour cells (TC-1 P0). These results provide the groundwork for future clinical development of the siRNA cocktail-mediated strategy by co-targeting immunosuppressive molecules to enhance the potency of DC-based vaccines.